Pengaruh Pengembangan Sumber Daya Manusia dan Budaya Organisasi Terhadap Kinerja Pegawai di Sekretariat DPRD Kota Ambon - Amaliah, Riski; Normawati, Normawati; Ufie, Josep A. (Jurnal Ilmiah Global Education, 2024)
This research aims to find out the Human Resource Development influences on the performance of employees in the Ambon City DPRD Secretariat; to know the organizational culture influence on the employee performance in the Secretariat of Ambon city DPRD; and to learn the development of human resources and the culture of the organization influence the workforce performance in Ambon town DPRD secretariat. The type of research in this study is qualitative descriptive research, with a population and sample of 53 employees (census method). This shows that the DPRD Secretariat gives an opportunity to officials who want to improve education and provide training in accordance with the Tupoxy, and by itself to influence the disadvantage of staff performance. Each employee has demonstrated a high level of work integrity in accordance with the characteristics of the organization, striving to be responsible in work, disciplined and result-oriented, thus contributing to improved employee performance. The development of human resources and organizational culture has influenced the improvement of staff performance in the Secretariat of the DPRD City of Ambon.